2016
DOI: 10.1063/1.4949265
|View full text |Cite
|
Sign up to set email alerts
|

High-performance beam steering using electrowetting-driven liquid prism fabricated by a simple dip-coating method

Abstract: A high degree of beam steering is demonstrated using an electrowetting-driven liquid prism. While prism devices have typically relied on complex and expensive laboratory setups, such as high-vacuum facilities for fabrication of dielectric layers, this work utilizes a simple dip-coating method to provide an ion gel layer as a dielectric, offering 2 or 3 orders higher specific capacitance (c ≈ 10 μF/cm2) than that of conventional dielectrics. Analytical studies present the effects of liquid selection and arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Figure 10d–f show the versatility of our prism arrays that are formed with the apex angles, ranging −20° ≤ ϕ ≤ 20° by varying the applied voltages at each of the prism sidewalls. By using two liquids with different refractive indices ( n air ≠ n 1 ≠ n 2 ), the previous studies have demonstrated beam steering of the incoming light that can be effectively achieved without the need of bulky mechanical moving parts [22,23,24]. Figure 11a shows an experimental demonstration of beam steering using a single liquid prism filled with high-reflective-index oil 1-bromonapthalene (liquid 1) and water (liquid 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 10d–f show the versatility of our prism arrays that are formed with the apex angles, ranging −20° ≤ ϕ ≤ 20° by varying the applied voltages at each of the prism sidewalls. By using two liquids with different refractive indices ( n air ≠ n 1 ≠ n 2 ), the previous studies have demonstrated beam steering of the incoming light that can be effectively achieved without the need of bulky mechanical moving parts [22,23,24]. Figure 11a shows an experimental demonstration of beam steering using a single liquid prism filled with high-reflective-index oil 1-bromonapthalene (liquid 1) and water (liquid 2).…”
Section: Resultsmentioning
confidence: 99%
“…This lab-on-a-wristband (LOW) concept highlights the potential of 3D EWOD technology for point-of-care (POC) applications. Another example of the 3D EWOD devices popularly studied in recent years is the liquid prism that enables spatial beam steering [18,19,20,21,22,23]. EWOD-driven liquid prism technology has been used in diverse applications including sunlight beam steering for solar energy harvesting [24,25,26] and optical beam control to achieve a Fresnel lens [23].…”
Section: Ion Gel Layer Coating For 3d Ewod Device Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, direct manipulation of discrete droplets enables fabrication and operation of highly automated microfluidics systems with more flexibility and higher efficiency [6][7][8][9][10][11][12]. Due to these unique advantages, EWOD digital microfluidics has been used for tremendous applications such as medical [13][14][15][16][17][18][19], display [20,21], optics [22,23], and cooling [24,25]. In addition, there are many recent EWOD studies on engineering applications such as optofluidics and solar energy [26,27].…”
Section: Introductionmentioning
confidence: 99%